The technical capabilities of the computer in enriching the creative design of talented students - Al-Ghamas, Hanan Saleh (Journal of Educational and Psychological Sciences, 2019)
This research aims to identify the technical capabilities of the computer in enriching the design of advertising, then apply it to talented students in the secondary stage using Photoshop program. The study applied the descriptive analytical method, and used the interview and the form of evaluation and analysis of the business tools for the study, and the sample of the study (5) of the talented students in art education and design in Dar Al Uloum Secondary School for Girls in Riyadh.
Keywords: technical capabilities; computers; design enrichment; advertising design; talented students